IMPLEMENTASI PENDEKATAN PROBLEM POSING DALAM MEWUJUDKAN ACTIVE JOYFULL EFFECTIVE LEARNING DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA - Mariyoto Mariyoto (Universitas Sarjanawiyata Tamansiswa, 2016)
The problem of the research is whether the effort of learning using AJEL (Active Joyfull Effective Learning) method can improve the student activity and achievement in class VII SMP N 3 Jatinom Klaten. The aim of the research is to design and apply the AJEL (Active Joyfull Effective Learning) in class VII SMP N 3 Jatinom Klaten to improve the student activity and achievement in math. The researcher did an action research through two cycles. Each cycles consist of: planning, action, observation and reflection. The technique of the data collection is through observation, questioner and test. The researcher analyze the data using test validity and reliability. The result of the research is that there is an improvement of the student activity and achievement to applying the AJEL (Active Joyfull Effective Learning) method in math.